The Value of the Interferon Inductors in the Treatment and Prevention of Respiratory Infections - O. V. Kladova; O. V. Molochkova; N. L. Waltz; Yu. V. Kompaniets; N. L. Grishkevich (LLC "Diagnostics and Vaccines", 2016)
The data on the causal effects of interferons (IFN) and interferon inductors on a wide range of respiratory viruses and stimulate the immune system. The mechanism of action of interferon inductors, provides an assessment of the efficacy and safety of domestic drug Amixin® (tiloron) for the treatment and prevention of acute respiratory viral infections and influenza in adults and children over 7 years. Application of Amixin® reduced the duration of the main symptoms of the disease contributed to the normalization of the immune status, reduced the incidence of SARS and influenza complications. Appointment of Amixin® in children older than 7 years with chronic herpes virus infection, has contributed to the clinical and laboratory remission and improvement of lymphocyte subpopulation composition.